LGG-14. LOGGIC (Low Grade Glioma in Children) Core BioClinical Data Bank: Establishment and added clinical value of an international molecular diagnostic registry for pediatric low-grade glioma patients. (3rd June 2022) - Hardin, Emily C; Schmid, Simone; Sommerkamp, Alexander; le Simon, Michè; Caspar, Claudia; Bodden, Carina; Heipertz, Anna-Elisa; Sievers, Philipp; Wittmann, Andrea; Perera, Ashwyn A; Milde, Till; Pfister, Stefan M; et al.
Abstract: BACKGROUND : The international, multicenter registry LOGGIC Core BioClinical Data Bank aims to enhance the understanding of tumor biology in pediatric low-grade glioma (pLGG) and provide clinical and molecular data. In addition to routine histopathological and molecular analyses, LOGGIC Core determines the driver alteration as precisely as possible to support treatment decisions and participation in interventional trials. Hence, the question arises whether comprehensive implementation of RNA sequencing using Fresh Frozen (FF) tumor tissue to identify underlying gene fusions improves diagnostic accuracy and provides a clinical benefit. METHODS : Establishment of an international molecular and clinical registry including the logistical and analytical pipeline. First analysis of all patients age 0 to 18, which were included in Germany as part of the German HIT-LOGGIC-program between April 2019 and February 2021, and for whom FF tissue was available. This included histopathological evaluation, immunohistochemistry, 850k methylation analysis, gene panel sequencing, RNA sequencing using FF tissue. RESULTS : FF tissue was available in 178/379 included cases. RNA sequencing was performed on 125 samples. In this prospective, population based cohort, we confirmed KIAA1549:BRAF-fusion (57%), BRAFV600E-mutation (9%) and FGFR1-changes (10%) as most frequent alterations. 12% of cases presented rare gene fusions (e.g. TPM3:NTRK1, EWSR1:VGLL1, GOPC:ROS1, SH3PXD2A:HTRA1, PDGFB:LRP1). In 19% of cases, RNA sequencing detected an actionable target not identified by conventional methods. CONCLUSION : The addition of RNA sequencing reveals clinically relevant alterations including rare gene fusions. By demonstrating improvement of diagnostic accuracy and making precision oncology studies (MEKi/RAFi/ERKi/NTRKi/FGFRi/ROSi) more accessible, the added value for pLGG patients becomes apparent. LOGGIC Core is currently being rolled out internationally and aims to define the new state of the art standard molecular diagnostics. We propose to include RNA sequencing as part of routine diagnostic procedures for all pLGG patients, especially in tumors where no common MAPK alteration was identified.